1998
DOI: 10.1111/j.1439-0485.1998.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Heterozygosity in a 12‐Month‐Old Cohort of Ostrea chilensis Obtained by Mass Spawning in the Laboratory

Abstract: Oysters (Osfrea chilensis PHILIPPI 1845). from a 40-month-old cohort which came from the natural population of the Quempillen River Estuary (Southern Chile), were used as parental stock (n = 600) for a hatchery-produced cohort. At 12 months of age this cohort was analysed physiologically (filtration rate, organic ingestion rate, absorption rate, assimilation efficiency, excretion rate, respiration rate) and electrophoretically (multilocus heterozygosity (MLH) using four loci: LAP, GPI, PGM, CA). Most physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
4
10
1
Order By: Relevance
“…Values are means ± SD (n = 5). Therefore, present results confirmed most earlier studies in bivalves reporting selection for faster growth to entail faster rates of feeding (Bayne, 1999a(Bayne, , 2000Bayne et al, 1999a,b;Holey and Foltz, 1987;Pernet et al, 2008;Tamayo et al, 2011Tamayo et al, , 2013Tamayo et al, , 2014Toro and Vergara, 1998), a physiological trait associated to larger gill areas in the present species of clams (Tamayo et al, 2011). Moreover, energy conversion efficiencies were higher in F, when compared to S clams, due to lower rates of metabolic energy expenditure per unit of metabolizable energy absorbed.…”
Section: Tablesupporting
confidence: 95%
See 3 more Smart Citations
“…Values are means ± SD (n = 5). Therefore, present results confirmed most earlier studies in bivalves reporting selection for faster growth to entail faster rates of feeding (Bayne, 1999a(Bayne, , 2000Bayne et al, 1999a,b;Holey and Foltz, 1987;Pernet et al, 2008;Tamayo et al, 2011Tamayo et al, , 2013Tamayo et al, , 2014Toro and Vergara, 1998), a physiological trait associated to larger gill areas in the present species of clams (Tamayo et al, 2011). Moreover, energy conversion efficiencies were higher in F, when compared to S clams, due to lower rates of metabolic energy expenditure per unit of metabolizable energy absorbed.…”
Section: Tablesupporting
confidence: 95%
“…It seems to be well established that increasing heterozygosity causes the reduction of the metabolic costs associated to protein deposition (Bayne and Hawkins, 1997;Hawkins et al, 1986Hawkins et al, , 1989 this being a physiological factor contributing to the maximization of energy budget in fast growing individuals. Although such association between faster growth and reduced rates of protein turnover would be expected to result in reduced basal or maintenance metabolic rates in fast growing specimens, available literature has provided contradictory results: for instances, Hawkins (1995), Hawkins and Day (1996); Garton et al (1984), Myrand et al (2009) found significantly lower maintenance metabolic rates in fast as compared to slow growers, however, such a relationship was not found in present study and many others (e.g., Bayne, 2000;Bayne et al, 1999b;Holey and Foltz, 1987;Pace et al, 2006;Tamayo et al, 2011Tamayo et al, , 2013Tamayo et al, , 2014Toro and Vergara, 1998). These studies were performed under different nutritional scenarios that ranged from hatchery conditions (food abundance) to natural conditions (more restrictive in terms of quantity and quality of available food).…”
Section: Acute and Acclimated Physiological Responses Of F And S Clamcontrasting
confidence: 78%
See 2 more Smart Citations
“…It is thought that increased growth in more heterozygous individuals is a result of increased metabolic efficiency ( e.g. reduced rates of oxygen consumption; Danzmann et al ., 1987; Toro & Vergara, 1998), increased growth efficiency (Toro & Vergara, 1998) or reduced rates of protein turnover (I.D. McCarthy, S.F.…”
Section: Discussionmentioning
confidence: 99%